Comparison of bimodal benefit for the use of DSL v5.0 and NAL-NL2 in cochlear implant listeners - Digeser, Frank; Engler, Max; Hoppe, Ulrich (International Journal of Audiology, 2019)
Objective: For a group of bimodal subjects with moderate to severe hearing loss contralateral to the cochlear implant (CI), the bimodal benefit of the hearing aid (HA) gain prescriptions DSL v5.0, NAL-NL2 and the recipients' own gain setting were assessed. Design: Speech perception in quiet and in noise as well as self-reported ratings of benefit were determined for all three gain-settings. Speech tests were performed in the bimodal, the HA alone and the CI alone condition. The bimodal benefit was assessed for each prescription as the difference score of the bimodal condition and the better ear. Study Sample: Twenty adults with post-lingual hearing loss. Results: Speech perception with DSL v5.0 was significantly higher compared to NAL-NL2 and the own prescription in both quiet and noise. The median bimodal benefit was highest for DSL v5.0 with an average of 15 percentage points for both words in quiet and sentences in noise. Conclusions: DSL v5.0 and NAL-NL2 are both suitable for HA fitting in bimodal users. For subjects with moderate to severe hearing loss and HA experience contralateral to the implanted side, DSL v5.0 may provide better speech perception and bimodal benefit.
CRIS-Team WoS Importer:2019-12-17